Natural convection and radiation in a radial porous fin with variable thermal conductivity - Darvishi, M.T.; Kani, F.; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
In this study, the effects of radiation and convection heat transfer in a radial porous fin are considered. The geometry considered is that of a rectangular profile fin. The porous fin allows the flow to infiltrate through it and solid-fluid interaction takes place. This study is performed using Darcy`s model to formulate the heat transfer equation. The thermal conductivity is assumed to be a function of temperature. The effects of the natural convection parameter "Nc", radiation parameter "Nr" and thermal conductivity parameter "m" on the dimensionless temperature distribution and heat transfer rate are discussed. The results suggest that the radiation transfers more heat than a similar model without radiation.
Keywords: porous radial fin; natural convection; radiation; thermal performance; spectral collocation method